:: Convergence and the Limit of Complex Sequences. Series
:: by Yasunari Shidama and Artur Korni{\l}owicz
::
:: Copyright (c) 1997-2017 Association of Mizar Users

Lm1: 0c = 0 + ()
;

theorem :: COMSEQ_3:1
for n being Nat holds
( n + 1 <> 0c & (n + 1) * <i> <> 0c ) ;

theorem Th2: :: COMSEQ_3:2
for rseq being Real_Sequence st ( for n being Nat holds rseq . n = 0 ) holds
for m being Nat holds (Partial_Sums (abs rseq)) . m = 0
proof end;

theorem Th3: :: COMSEQ_3:3
for rseq being Real_Sequence st ( for n being Nat holds rseq . n = 0 ) holds
rseq is absolutely_summable
proof end;

set C = seq_const 0;

Lm2: for n being Nat holds () . n = 0
by SEQ_1:57;

registration
coherence
for b1 being Real_Sequence st b1 is summable holds
b1 is convergent
by SERIES_1:4;
end;

registration
coherence
for b1 being Real_Sequence st b1 is absolutely_summable holds
b1 is summable
;
end;

registration
existence
ex b1 being Real_Sequence st b1 is absolutely_summable
by ;
end;

theorem :: COMSEQ_3:4
for rseq being Real_Sequence st rseq is convergent holds
for p being Real st 0 < p holds
ex n being Nat st
for m, l being Nat st n <= m & n <= l holds
|.((rseq . m) - (rseq . l)).| < p
proof end;

theorem :: COMSEQ_3:5
for rseq being Real_Sequence
for p being Real st ( for n being Nat holds rseq . n <= p ) holds
for n, l being Nat holds ((Partial_Sums rseq) . (n + l)) - ((Partial_Sums rseq) . n) <= p * l
proof end;

theorem :: COMSEQ_3:6
for rseq being Real_Sequence
for p being Real st ( for n being Nat holds rseq . n <= p ) holds
for n being Nat holds (Partial_Sums rseq) . n <= p * (n + 1)
proof end;

theorem :: COMSEQ_3:7
for rseq1, rseq2 being Real_Sequence
for m being Nat
for p being Real st ( for n being Nat st n <= m holds
rseq1 . n <= p * (rseq2 . n) ) holds
(Partial_Sums rseq1) . m <= p * ((Partial_Sums rseq2) . m)
proof end;

theorem :: COMSEQ_3:8
for rseq1, rseq2 being Real_Sequence
for m being Nat
for p being Real st ( for n being Nat st n <= m holds
rseq1 . n <= p * (rseq2 . n) ) holds
for n, l being Nat st n + l <= m holds
((Partial_Sums rseq1) . (n + l)) - ((Partial_Sums rseq1) . n) <= p * (((Partial_Sums rseq2) . (n + l)) - ((Partial_Sums rseq2) . n))
proof end;

theorem :: COMSEQ_3:9
for rseq being Real_Sequence st ( for n being Nat holds 0 <= rseq . n ) holds
( ( for n, m being Nat st n <= m holds
|.(((Partial_Sums rseq) . m) - ((Partial_Sums rseq) . n)).| = ((Partial_Sums rseq) . m) - ((Partial_Sums rseq) . n) ) & ( for n being Nat holds |.((Partial_Sums rseq) . n).| = (Partial_Sums rseq) . n ) )
proof end;

theorem :: COMSEQ_3:10
for seq1, seq2 being Complex_Sequence st seq1 is convergent & seq2 is convergent & lim (seq1 - seq2) = 0c holds
lim seq1 = lim seq2
proof end;

Lm3: for seq being Complex_Sequence
for n being Nat holds
( |.(seq . n).| = |.seq.| . n & 0 <= |.seq.| . n )

proof end;

definition
let z be Complex;
func z GeoSeq -> Complex_Sequence means :Def1: :: COMSEQ_3:def 1
( it . 0 = 1r & ( for n being Nat holds it . (n + 1) = (it . n) * z ) );
existence
ex b1 being Complex_Sequence st
( b1 . 0 = 1r & ( for n being Nat holds b1 . (n + 1) = (b1 . n) * z ) )
proof end;
uniqueness
for b1, b2 being Complex_Sequence st b1 . 0 = 1r & ( for n being Nat holds b1 . (n + 1) = (b1 . n) * z ) & b2 . 0 = 1r & ( for n being Nat holds b2 . (n + 1) = (b2 . n) * z ) holds
b1 = b2
proof end;
end;

:: deftheorem Def1 defines GeoSeq COMSEQ_3:def 1 :
for z being Complex
for b2 being Complex_Sequence holds
( b2 = z GeoSeq iff ( b2 . 0 = 1r & ( for n being Nat holds b2 . (n + 1) = (b2 . n) * z ) ) );

definition
let z be Complex;
let n be Nat;
:: original: |^
redefine func z |^ n -> Element of COMPLEX equals :: COMSEQ_3:def 2
() . n;
coherence
z |^ n is Element of COMPLEX
by XCMPLX_0:def 2;
compatibility
for b1 being Element of COMPLEX holds
( b1 = z |^ n iff b1 = () . n )
proof end;
end;

:: deftheorem defines |^ COMSEQ_3:def 2 :
for z being Complex
for n being Nat holds z |^ n = () . n;

theorem :: COMSEQ_3:11
for z being Complex holds z |^ 0 = 1r by ;

definition
let f be complex-valued Function;
set A = dom f;
deffunc H1( object ) -> Element of REAL = Re (f . \$1);
func Re f -> Function means :Def3: :: COMSEQ_3:def 3
( dom it = dom f & ( for x being object st x in dom it holds
it . x = Re (f . x) ) );
existence
ex b1 being Function st
( dom b1 = dom f & ( for x being object st x in dom b1 holds
b1 . x = Re (f . x) ) )
proof end;
uniqueness
for b1, b2 being Function st dom b1 = dom f & ( for x being object st x in dom b1 holds
b1 . x = Re (f . x) ) & dom b2 = dom f & ( for x being object st x in dom b2 holds
b2 . x = Re (f . x) ) holds
b1 = b2
proof end;
deffunc H2( object ) -> Element of REAL = Im (f . \$1);
func Im f -> Function means :Def4: :: COMSEQ_3:def 4
( dom it = dom f & ( for x being object st x in dom it holds
it . x = Im (f . x) ) );
existence
ex b1 being Function st
( dom b1 = dom f & ( for x being object st x in dom b1 holds
b1 . x = Im (f . x) ) )
proof end;
uniqueness
for b1, b2 being Function st dom b1 = dom f & ( for x being object st x in dom b1 holds
b1 . x = Im (f . x) ) & dom b2 = dom f & ( for x being object st x in dom b2 holds
b2 . x = Im (f . x) ) holds
b1 = b2
proof end;
end;

:: deftheorem Def3 defines Re COMSEQ_3:def 3 :
for f being complex-valued Function
for b2 being Function holds
( b2 = Re f iff ( dom b2 = dom f & ( for x being object st x in dom b2 holds
b2 . x = Re (f . x) ) ) );

:: deftheorem Def4 defines Im COMSEQ_3:def 4 :
for f being complex-valued Function
for b2 being Function holds
( b2 = Im f iff ( dom b2 = dom f & ( for x being object st x in dom b2 holds
b2 . x = Im (f . x) ) ) );

registration
let f be complex-valued Function;
coherence
proof end;
coherence
proof end;
end;

definition
let X be set ;
let f be PartFunc of X,COMPLEX;
:: original: Re
redefine func Re f -> PartFunc of X,REAL;
coherence
Re f is PartFunc of X,REAL
proof end;
:: original: Im
redefine func Im f -> PartFunc of X,REAL;
coherence
Im f is PartFunc of X,REAL
proof end;
end;

definition
let c be Complex_Sequence;
:: original: Re
redefine func Re c -> Real_Sequence means :Def5: :: COMSEQ_3:def 5
for n being Nat holds it . n = Re (c . n);
coherence
proof end;
compatibility
for b1 being Real_Sequence holds
( b1 = Re c iff for n being Nat holds b1 . n = Re (c . n) )
proof end;
:: original: Im
redefine func Im c -> Real_Sequence means :Def6: :: COMSEQ_3:def 6
for n being Nat holds it . n = Im (c . n);
coherence
proof end;
compatibility
for b1 being Real_Sequence holds
( b1 = Im c iff for n being Nat holds b1 . n = Im (c . n) )
proof end;
end;

:: deftheorem Def5 defines Re COMSEQ_3:def 5 :
for c being Complex_Sequence
for b2 being Real_Sequence holds
( b2 = Re c iff for n being Nat holds b2 . n = Re (c . n) );

:: deftheorem Def6 defines Im COMSEQ_3:def 6 :
for c being Complex_Sequence
for b2 being Real_Sequence holds
( b2 = Im c iff for n being Nat holds b2 . n = Im (c . n) );

theorem Th12: :: COMSEQ_3:12
for z being Complex holds |.z.| <= |.(Re z).| + |.(Im z).|
proof end;

theorem Th13: :: COMSEQ_3:13
for z being Complex holds
( |.(Re z).| <= |.z.| & |.(Im z).| <= |.z.| )
proof end;

theorem Th14: :: COMSEQ_3:14
for seq1, seq2 being Complex_Sequence st Re seq1 = Re seq2 & Im seq1 = Im seq2 holds
seq1 = seq2
proof end;

theorem Th15: :: COMSEQ_3:15
for seq1, seq2 being Complex_Sequence holds
( (Re seq1) + (Re seq2) = Re (seq1 + seq2) & (Im seq1) + (Im seq2) = Im (seq1 + seq2) )
proof end;

theorem Th16: :: COMSEQ_3:16
for seq being Complex_Sequence holds
( - (Re seq) = Re (- seq) & - (Im seq) = Im (- seq) )
proof end;

theorem Th17: :: COMSEQ_3:17
for r being Real
for z being Complex holds
( r * (Re z) = Re (r * z) & r * (Im z) = Im (r * z) )
proof end;

theorem Th18: :: COMSEQ_3:18
for seq1, seq2 being Complex_Sequence holds
( (Re seq1) - (Re seq2) = Re (seq1 - seq2) & (Im seq1) - (Im seq2) = Im (seq1 - seq2) )
proof end;

theorem :: COMSEQ_3:19
for seq being Complex_Sequence
for r being Real holds
( r (#) (Re seq) = Re (r (#) seq) & r (#) (Im seq) = Im (r (#) seq) )
proof end;

theorem :: COMSEQ_3:20
for seq being Complex_Sequence
for z being Complex holds
( Re (z (#) seq) = ((Re z) (#) (Re seq)) - ((Im z) (#) (Im seq)) & Im (z (#) seq) = ((Re z) (#) (Im seq)) + ((Im z) (#) (Re seq)) )
proof end;

theorem :: COMSEQ_3:21
for seq1, seq2 being Complex_Sequence holds
( Re (seq1 (#) seq2) = ((Re seq1) (#) (Re seq2)) - ((Im seq1) (#) (Im seq2)) & Im (seq1 (#) seq2) = ((Re seq1) (#) (Im seq2)) + ((Im seq1) (#) (Re seq2)) )
proof end;

definition
let Nseq be increasing sequence of NAT;
let seq be Complex_Sequence;
:: original: (#)
redefine func seq * Nseq -> Complex_Sequence;
coherence
Nseq (#) seq is Complex_Sequence
proof end;
end;

theorem Th22: :: COMSEQ_3:22
for seq being Complex_Sequence
for Nseq being increasing sequence of NAT holds
( Re (seq * Nseq) = (Re seq) * Nseq & Im (seq * Nseq) = (Im seq) * Nseq )
proof end;

theorem Th23: :: COMSEQ_3:23
for seq being Complex_Sequence
for k being Nat holds
( (Re seq) ^\ k = Re (seq ^\ k) & (Im seq) ^\ k = Im (seq ^\ k) )
proof end;

definition
let s be Complex_Sequence;
:: original: Partial_Sums
redefine func Partial_Sums s -> Complex_Sequence;
coherence
proof end;
end;

definition
let seq be Complex_Sequence;
func Sum seq -> Element of COMPLEX equals :: COMSEQ_3:def 7
lim (Partial_Sums seq);
coherence
lim (Partial_Sums seq) is Element of COMPLEX
by XCMPLX_0:def 2;
end;

:: deftheorem defines Sum COMSEQ_3:def 7 :
for seq being Complex_Sequence holds Sum seq = lim (Partial_Sums seq);

theorem Th24: :: COMSEQ_3:24
for seq being Complex_Sequence st ( for n being Nat holds seq . n = 0c ) holds
for m being Nat holds (Partial_Sums seq) . m = 0c
proof end;

theorem Th25: :: COMSEQ_3:25
for seq being Complex_Sequence st ( for n being Nat holds seq . n = 0c ) holds
for m being Nat holds () . m = 0
proof end;

theorem Th26: :: COMSEQ_3:26
for seq being Complex_Sequence holds
( Partial_Sums (Re seq) = Re (Partial_Sums seq) & Partial_Sums (Im seq) = Im (Partial_Sums seq) )
proof end;

theorem Th27: :: COMSEQ_3:27
for seq1, seq2 being Complex_Sequence holds (Partial_Sums seq1) + (Partial_Sums seq2) = Partial_Sums (seq1 + seq2) by SERIES_1:5;

theorem Th28: :: COMSEQ_3:28
for seq1, seq2 being Complex_Sequence holds (Partial_Sums seq1) - (Partial_Sums seq2) = Partial_Sums (seq1 - seq2)
proof end;

theorem Th29: :: COMSEQ_3:29
for seq being Complex_Sequence
for z being Complex holds Partial_Sums (z (#) seq) = z (#) (Partial_Sums seq)
proof end;

theorem :: COMSEQ_3:30
for seq being Complex_Sequence
for k being Nat holds |.((Partial_Sums seq) . k).| <= () . k
proof end;

theorem Th31: :: COMSEQ_3:31
for seq being Complex_Sequence
for n, m being Nat holds |.(((Partial_Sums seq) . m) - ((Partial_Sums seq) . n)).| <= |.((() . m) - (() . n)).|
proof end;

theorem Th32: :: COMSEQ_3:32
for seq being Complex_Sequence
for k being Nat holds
( (Partial_Sums (Re seq)) ^\ k = Re ((Partial_Sums seq) ^\ k) & (Partial_Sums (Im seq)) ^\ k = Im ((Partial_Sums seq) ^\ k) )
proof end;

theorem :: COMSEQ_3:33
for seq, seq1 being Complex_Sequence st ( for n being Nat holds seq1 . n = seq . 0 ) holds
Partial_Sums (seq ^\ 1) = ((Partial_Sums seq) ^\ 1) - seq1
proof end;

theorem Th34: :: COMSEQ_3:34
for seq being Complex_Sequence holds Partial_Sums |.seq.| is non-decreasing
proof end;

registration
let seq be Complex_Sequence;
coherence
for b1 being Real_Sequence st b1 = Partial_Sums |.seq.| holds
b1 is non-decreasing
by Th34;
end;

theorem :: COMSEQ_3:35
for seq1, seq2 being Complex_Sequence
for m being Nat st ( for n being Nat st n <= m holds
seq1 . n = seq2 . n ) holds
(Partial_Sums seq1) . m = (Partial_Sums seq2) . m
proof end;

theorem Th36: :: COMSEQ_3:36
for z being Complex st 1r <> z holds
for n being Nat holds () . n = (1r - (z |^ (n + 1))) / (1r - z)
proof end;

theorem Th37: :: COMSEQ_3:37
for seq being Complex_Sequence
for z being Complex st z <> 1r & ( for n being Nat holds seq . (n + 1) = z * (seq . n) ) holds
for n being Nat holds (Partial_Sums seq) . n = (seq . 0) * ((1r - (z |^ (n + 1))) / (1r - z))
proof end;

theorem Th38: :: COMSEQ_3:38
for a, b being Real_Sequence
for c being Complex_Sequence st ( for n being Nat holds
( Re (c . n) = a . n & Im (c . n) = b . n ) ) holds
( ( a is convergent & b is convergent ) iff c is convergent )
proof end;

theorem Th39: :: COMSEQ_3:39
for a, b being convergent Real_Sequence
for c being Complex_Sequence st ( for n being Nat holds
( Re (c . n) = a . n & Im (c . n) = b . n ) ) holds
( c is convergent & lim c = (lim a) + ((lim b) * <i>) )
proof end;

theorem Th40: :: COMSEQ_3:40
for a, b being Real_Sequence
for c being convergent Complex_Sequence st ( for n being Nat holds
( Re (c . n) = a . n & Im (c . n) = b . n ) ) holds
( a is convergent & b is convergent & lim a = Re (lim c) & lim b = Im (lim c) )
proof end;

theorem Th41: :: COMSEQ_3:41
for c being convergent Complex_Sequence holds
( Re c is convergent & Im c is convergent & lim (Re c) = Re (lim c) & lim (Im c) = Im (lim c) )
proof end;

registration
let c be convergent Complex_Sequence;
coherence
for b1 being Real_Sequence st b1 = Re c holds
b1 is convergent
by Th41;
coherence
for b1 being Real_Sequence st b1 = Im c holds
b1 is convergent
by Th41;
end;

theorem Th42: :: COMSEQ_3:42
for c being Complex_Sequence st Re c is convergent & Im c is convergent holds
( c is convergent & Re (lim c) = lim (Re c) & Im (lim c) = lim (Im c) )
proof end;

theorem Th43: :: COMSEQ_3:43
for seq being Complex_Sequence
for z being Complex st 0 < |.z.| & |.z.| < 1 & seq . 0 = z & ( for n being Nat holds seq . (n + 1) = (seq . n) * z ) holds
( seq is convergent & lim seq = 0c )
proof end;

theorem Th44: :: COMSEQ_3:44
for seq being Complex_Sequence
for z being Complex st |.z.| < 1 & ( for n being Nat holds seq . n = z |^ (n + 1) ) holds
( seq is convergent & lim seq = 0c )
proof end;

theorem :: COMSEQ_3:45
for seq being Complex_Sequence
for r being Real st r > 0 & ex m being Nat st
for n being Nat st n >= m holds
|.(seq . n).| >= r & |.seq.| is convergent holds
lim |.seq.| <> 0
proof end;

theorem Th46: :: COMSEQ_3:46
for seq being Complex_Sequence holds
( seq is convergent iff for p being Real st 0 < p holds
ex n being Nat st
for m being Nat st n <= m holds
|.((seq . m) - (seq . n)).| < p )
proof end;

theorem :: COMSEQ_3:47
for seq being Complex_Sequence st seq is convergent holds
for p being Real st 0 < p holds
ex n being Nat st
for m, l being Nat st n <= m & n <= l holds
|.((seq . m) - (seq . l)).| < p
proof end;

theorem :: COMSEQ_3:48
for rseq being Real_Sequence
for seq being Complex_Sequence st ( for n being Nat holds |.(seq . n).| <= rseq . n ) & rseq is convergent & lim rseq = 0 holds
( seq is convergent & lim seq = 0c )
proof end;

theorem :: COMSEQ_3:49
for seq, seq1 being Complex_Sequence st seq is subsequence of seq1 holds
( Re seq is subsequence of Re seq1 & Im seq is subsequence of Im seq1 )
proof end;

theorem :: COMSEQ_3:50
for seq being Complex_Sequence st seq is bounded holds
ex seq1 being Complex_Sequence st
( seq1 is subsequence of seq & seq1 is convergent )
proof end;

definition
let seq be Complex_Sequence;
attr seq is summable means :Def8: :: COMSEQ_3:def 8
Partial_Sums seq is convergent ;
end;

:: deftheorem Def8 defines summable COMSEQ_3:def 8 :
for seq being Complex_Sequence holds
( seq is summable iff Partial_Sums seq is convergent );

set D = NAT --> 0c;

registration
existence
ex b1 being Complex_Sequence st b1 is summable
proof end;
end;

registration
let seq be summable Complex_Sequence;
coherence
for b1 being Complex_Sequence st b1 = Partial_Sums seq holds
b1 is convergent
by Def8;
end;

definition
let seq be Complex_Sequence;
attr seq is absolutely_summable means :Def9: :: COMSEQ_3:def 9
|.seq.| is summable ;
end;

:: deftheorem Def9 defines absolutely_summable COMSEQ_3:def 9 :
for seq being Complex_Sequence holds
( seq is absolutely_summable iff |.seq.| is summable );

theorem Th51: :: COMSEQ_3:51
for seq being Complex_Sequence st ( for n being Nat holds seq . n = 0c ) holds
seq is absolutely_summable
proof end;

registration
existence
ex b1 being Complex_Sequence st b1 is absolutely_summable
proof end;
end;

registration
let seq be absolutely_summable Complex_Sequence;
cluster |.seq.| -> summable for Real_Sequence;
coherence
for b1 being Real_Sequence st b1 = |.seq.| holds
b1 is summable
by Def9;
end;

theorem Th52: :: COMSEQ_3:52
for seq being Complex_Sequence st seq is summable holds
( seq is convergent & lim seq = 0c )
proof end;

registration
coherence
for b1 being Complex_Sequence st b1 is summable holds
b1 is convergent
by Th52;
end;

theorem Th53: :: COMSEQ_3:53
for seq being Complex_Sequence st seq is summable holds
( Re seq is summable & Im seq is summable & Sum seq = (Sum (Re seq)) + ((Sum (Im seq)) * <i>) )
proof end;

registration
let seq be summable Complex_Sequence;
cluster Re seq -> summable for Real_Sequence;
coherence
for b1 being Real_Sequence st b1 = Re seq holds
b1 is summable
by Th53;
cluster Im seq -> summable for Real_Sequence;
coherence
for b1 being Real_Sequence st b1 = Im seq holds
b1 is summable
by Th53;
end;

theorem Th54: :: COMSEQ_3:54
for seq1, seq2 being Complex_Sequence st seq1 is summable & seq2 is summable holds
( seq1 + seq2 is summable & Sum (seq1 + seq2) = (Sum seq1) + (Sum seq2) )
proof end;

theorem Th55: :: COMSEQ_3:55
for seq1, seq2 being Complex_Sequence st seq1 is summable & seq2 is summable holds
( seq1 - seq2 is summable & Sum (seq1 - seq2) = (Sum seq1) - (Sum seq2) )
proof end;

registration
let seq1, seq2 be summable Complex_Sequence;
cluster seq1 + seq2 -> summable for Complex_Sequence;
coherence
for b1 being Complex_Sequence st b1 = seq1 + seq2 holds
b1 is summable
by Th54;
cluster seq1 - seq2 -> summable for Complex_Sequence;
coherence
for b1 being Complex_Sequence st b1 = seq1 - seq2 holds
b1 is summable
by Th55;
end;

theorem Th56: :: COMSEQ_3:56
for seq being Complex_Sequence st seq is summable holds
for z being Complex holds
( z (#) seq is summable & Sum (z (#) seq) = z * (Sum seq) )
proof end;

registration
let z be Element of COMPLEX ;
let seq be summable Complex_Sequence;
cluster z (#) seq -> summable for Complex_Sequence;
coherence
for b1 being Complex_Sequence st b1 = z (#) seq holds
b1 is summable
by Th56;
end;

theorem Th57: :: COMSEQ_3:57
for seq being Complex_Sequence st Re seq is summable & Im seq is summable holds
( seq is summable & Sum seq = (Sum (Re seq)) + ((Sum (Im seq)) * <i>) )
proof end;

theorem Th58: :: COMSEQ_3:58
for seq being Complex_Sequence st seq is summable holds
for n being Nat holds seq ^\ n is summable
proof end;

registration
let seq be summable Complex_Sequence;
let n be Nat;
cluster seq ^\ n -> summable for Complex_Sequence;
coherence
for b1 being Complex_Sequence st b1 = seq ^\ n holds
b1 is summable
by Th58;
end;

theorem :: COMSEQ_3:59
for seq being Complex_Sequence st ex n being Nat st seq ^\ n is summable holds
seq is summable
proof end;

theorem :: COMSEQ_3:60
for seq being Complex_Sequence st seq is summable holds
for n being Nat holds Sum seq = ((Partial_Sums seq) . n) + (Sum (seq ^\ (n + 1)))
proof end;

theorem Th61: :: COMSEQ_3:61
for seq being Complex_Sequence holds
( Partial_Sums |.seq.| is bounded_above iff seq is absolutely_summable )
proof end;

registration
let seq be absolutely_summable Complex_Sequence;
coherence
for b1 being Real_Sequence st b1 = Partial_Sums |.seq.| holds
b1 is bounded_above
by Th61;
end;

theorem Th62: :: COMSEQ_3:62
for seq being Complex_Sequence holds
( seq is summable iff for p being Real st 0 < p holds
ex n being Nat st
for m being Nat st n <= m holds
|.(((Partial_Sums seq) . m) - ((Partial_Sums seq) . n)).| < p ) by Th46;

theorem Th63: :: COMSEQ_3:63
for seq being Complex_Sequence st seq is absolutely_summable holds
seq is summable
proof end;

registration
coherence
for b1 being Complex_Sequence st b1 is absolutely_summable holds
b1 is summable
by Th63;
end;

registration
existence
ex b1 being Complex_Sequence st b1 is absolutely_summable
proof end;
end;

theorem Th64: :: COMSEQ_3:64
for z being Complex st |.z.| < 1 holds
( z GeoSeq is summable & Sum () = 1r / (1r - z) )
proof end;

theorem :: COMSEQ_3:65
for seq being Complex_Sequence
for z being Complex st |.z.| < 1 & ( for n being Nat holds seq . (n + 1) = z * (seq . n) ) holds
( seq is summable & Sum seq = (seq . 0) / (1r - z) )
proof end;

theorem :: COMSEQ_3:66
for rseq1 being Real_Sequence
for seq2 being Complex_Sequence st rseq1 is summable & ex m being Nat st
for n being Nat st m <= n holds
|.(seq2 . n).| <= rseq1 . n holds
seq2 is absolutely_summable
proof end;

theorem :: COMSEQ_3:67
for seq1, seq2 being Complex_Sequence st ( for n being Nat holds
( 0 <= |.seq1.| . n & |.seq1.| . n <= |.seq2.| . n ) ) & seq2 is absolutely_summable holds
( seq1 is absolutely_summable & Sum |.seq1.| <= Sum |.seq2.| ) by SERIES_1:20;

theorem :: COMSEQ_3:68
for seq being Complex_Sequence st ( for n being Nat holds |.seq.| . n > 0 ) & ex m being Nat st
for n being Nat st n >= m holds
(|.seq.| . (n + 1)) / (|.seq.| . n) >= 1 holds
not seq is absolutely_summable by SERIES_1:27;

theorem :: COMSEQ_3:69
for rseq1 being Real_Sequence
for seq being Complex_Sequence st ( for n being Nat holds rseq1 . n = n -root (|.seq.| . n) ) & rseq1 is convergent & lim rseq1 < 1 holds
seq is absolutely_summable
proof end;

theorem :: COMSEQ_3:70
for rseq1 being Real_Sequence
for seq being Complex_Sequence st ( for n being Nat holds rseq1 . n = n -root (|.seq.| . n) ) & ex m being Nat st
for n being Nat st m <= n holds
rseq1 . n >= 1 holds
not |.seq.| is summable
proof end;

theorem :: COMSEQ_3:71
for rseq1 being Real_Sequence
for seq being Complex_Sequence st ( for n being Nat holds rseq1 . n = n -root (|.seq.| . n) ) & rseq1 is convergent & lim rseq1 > 1 holds
not seq is absolutely_summable
proof end;

theorem :: COMSEQ_3:72
for rseq1 being Real_Sequence
for seq being Complex_Sequence st |.seq.| is non-increasing & ( for n being Nat holds rseq1 . n = (2 to_power n) * (|.seq.| . (2 to_power n)) ) holds
( seq is absolutely_summable iff rseq1 is summable )
proof end;

theorem :: COMSEQ_3:73
for seq being Complex_Sequence
for p being Real st p > 1 & ( for n being Nat st n >= 1 holds
|.seq.| . n = 1 / (n to_power p) ) holds
seq is absolutely_summable by SERIES_1:32;

theorem :: COMSEQ_3:74
for seq being Complex_Sequence
for p being Real st p <= 1 & ( for n being Nat st n >= 1 holds
|.seq.| . n = 1 / (n to_power p) ) holds
not seq is absolutely_summable by SERIES_1:33;

theorem :: COMSEQ_3:75
for rseq1 being Real_Sequence
for seq being Complex_Sequence st ( for n being Nat holds
( seq . n <> 0c & rseq1 . n = (|.seq.| . (n + 1)) / (|.seq.| . n) ) ) & rseq1 is convergent & lim rseq1 < 1 holds
seq is absolutely_summable
proof end;

theorem :: COMSEQ_3:76
for seq being Complex_Sequence st ( for n being Nat holds seq . n <> 0c ) & ex m being Nat st
for n being Nat st n >= m holds
(|.seq.| . (n + 1)) / (|.seq.| . n) >= 1 holds
not seq is absolutely_summable
proof end;